2021
DOI: 10.1002/tpg2.20169
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of somatic mutations leads to genetic mosaicism in cannabis

Abstract: Cannabis (Cannabis sativa L.) is typically propagated using stem cuttings taken from mother plants to produce genetically uniform propagules. However, producers anecdotally report that clonal lines deteriorate over time and eventually produce clones with less vigor and lower cannabinoid levels than the original mother plant. While the cause of this deterioration has not been investigated, one potential contributor is the accumulation of somatic mutations within the plant. To test this, we used deep sequencing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Worldwide cannabis cultivation has increased due to the recent changes in legalization, regulation and marketization of Cannabis sativa L. for industrial, medicinal and recreational use [ 1 , 2 ]. To date, 177 phytocannabinoids have been identified in cannabis plants [ 3 ], among which the two most abundant are the psychoactive compound Δ 9 -tetrahydrocannabinol (THC) and the non-psychoactive cannabidiol (CBD) [ 4 ]—whose medical properties have accumulated evidence for decades [ 5 , 6 ]. Both compounds have shown pharmacological effects for several medical treatments [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide cannabis cultivation has increased due to the recent changes in legalization, regulation and marketization of Cannabis sativa L. for industrial, medicinal and recreational use [ 1 , 2 ]. To date, 177 phytocannabinoids have been identified in cannabis plants [ 3 ], among which the two most abundant are the psychoactive compound Δ 9 -tetrahydrocannabinol (THC) and the non-psychoactive cannabidiol (CBD) [ 4 ]—whose medical properties have accumulated evidence for decades [ 5 , 6 ]. Both compounds have shown pharmacological effects for several medical treatments [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional cutting methods used for cannabis are time-consuming and associated with a wide range of diseases (e.g., viruses, bacteria, and fungi) that hamper the phytosanitary quality of the plants obtained [ 7 ]. While vegetative propagation through cuttings theoretically produces plants that are phenotypically and genetically identical to their mother plants, cannabis producers have noted that cuttings taken from mother plants change over time and generally become less vigorous with lower levels of cannabinoids [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, based on the explant source, in vitro plant rejuvenation is accompanied by specific changes in gene expression patterns and epigenetic regulation, which finally lead to different phenotypical changes such as phyllotaxy, the shape and size of leaves, as well as the capacity for multiplication [ 26 ]. In relation to cannabis, Adamek et al [ 8 ] previously showed that the accumulation of somatic mutations in top-part-derived cuttings was significantly higher than in bottom-part-derived cuttings from the cannabis mother plant, showing the importance of explant source. The physical position and age of the explant largely impact the composition of internal phytohormones, which can influence tissue responsiveness [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds accumulate mainly in the glandular trichomes of the female plant 2 . To date, 177 phytocannabinoids have been identified among which the two well‐known cannabinoids, to which medical properties or health claims are assigned: the psychoactive substance Δ 9 ‐tetrahydrocannabinol (THC) and cannabidiol (CBD) 3 . They are synthetized as carboxylic acids and decarboxylated to the neutral form during exposure to light, heat, or prolonged storage; Δ 9 ‐tetrahydrocannabinolic acid (THCA) is decarboxylated to THC, and cannabidiolic acid (CBDA) is decarboxylated to CBD 4 …”
Section: Introductionmentioning
confidence: 99%